2014
DOI: 10.4049/jimmunol.1300968
|View full text |Cite
|
Sign up to set email alerts
|

Role for σ38 in Prolonged Survival of Escherichia coli in Drosophila melanogaster

Abstract: Bacteria adapt themselves to host environments by altering the pattern of gene expression. The promoter-recognizing subunit σ of bacterial RNA polymerase plays a major role in the selection of genes to be transcribed. Among seven σ factors of Escherichia coli, σ38 is responsible for the transcription of genes in the stationary phase and under stressful conditions. We found a transient increase of σ38 when E. coli was injected into the hemocoel of Drosophila melanogaster. The loss of σ38 made E. coli rapidly el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 55 publications
(90 reference statements)
1
13
0
Order By: Relevance
“…All procedures were performed as described previously (41,44). In brief, male adult flies, 3-7 d after eclosion (15-20 flies per vial, one to three vials in each experiment), were anesthetized with CO 2 and abdominally injected with 50 nl of PBS containing a given number of bacteria (stated in each figure) with the aid of a nitrogen gas-operated microinjector (Narishige, Tokyo, Japan).…”
Section: Bacterial Infection and Assays For Colony-forming Bacteria Amentioning
confidence: 99%
See 4 more Smart Citations
“…All procedures were performed as described previously (41,44). In brief, male adult flies, 3-7 d after eclosion (15-20 flies per vial, one to three vials in each experiment), were anesthetized with CO 2 and abdominally injected with 50 nl of PBS containing a given number of bacteria (stated in each figure) with the aid of a nitrogen gas-operated microinjector (Narishige, Tokyo, Japan).…”
Section: Bacterial Infection and Assays For Colony-forming Bacteria Amentioning
confidence: 99%
“…Once bound by bacterial substances, the receptors activate signaling pathways in immune cells to induce antibacterial reactions, including the production of antimicrobial peptides and the phagocytosis of bacteria (38)(39)(40). E. coli is generally considered to be nonpathogenic in Drosophila, but our previous study showed that a high load of E. coli may kill flies (41). Under such conditions, the Imd pathway, which is responsible for the production of antimicrobial peptides, and phagocytosis by hemocytes are required for the long survival of adult flies after infection with E. coli (41), suggesting the involvement of both humoral and cellular immune responses in the protection of Drosophila from pathogenic infection with E. coli.…”
mentioning
confidence: 99%
See 3 more Smart Citations